Adaptive assessment model in Moodle - Lieponienė, Jurgita; Kulvietienė , Regina (Lietuvos matematikos rinkinys, 2009)
Article analyses an adaptive knowledge assessment. Referring to defined criteria the virtual learning environments such as Blackboard Learning System Vista, Workplace Collaboration Learning System and adaptability of testing system Moodle are evaluated. Is fully described a produced adaptive valued activity model in the virtual learning system Moodle that was created following the Bloom’s taxonomy levels and using one of virtual learning environment Moodle activities – a lesson activity.
Keywords: virtual learning environment; adaptive knowledge evaluation; adaptive testing system; knowledge evaluation tools